Effects of the Fertilizer Added with DMPP on Soil Nitrous Oxide Emissions and Microbial Functional Diversity - Anna Tedeschi; Anna De Marco; Franca Polimeno; Paul Di Tommasi; Giuseppe Maglione; Lucia Ottaiano; Carmen Arena; Vincenzo Magliulo; Luca Vitale (Agriculture, 2020)
Agricultural sites contribute extensively to atmospheric emissions of climate-altering gases such as nitrous oxide. Several strategies have been considered to mitigate the impact of agriculture on climate, among these the utilization of fertilizers added with nitrification inhibitors such as DMPP (3,4-dimethylpyrazole phosphate) may represent a suitable solution. DMPP inhibits the growth and activity of ammonia-oxidizing microorganisms, particularly the ammonia-oxidizing bacteria, which are involved in N2O production. At present, little information is available on the effects of DMPP on the catabolic diversity of soil microbial community. In this study, the N2O emission by soil was performed by using the static chamber technique. The biological determinations of the microbial biomass carbon and the catabolic profile were assessed by measuring the substrate-induced respiration during the entire growing season of a potato crop under two nitrogen treatments: fertilization with and without DMPP. Our results did not show a clear mitigation of N2O emission by DMPP, even if a tendency to lower N2O fluxes in DMPP plots occurred when soil temperatures were lower than 20 °C. Conversely, DMPP deeply affected the microbial biomass and the catabolism of soil microorganisms, exerting a negative effect when it accumulated in excessive doses in the soil, limiting the growth and the capacity of soil microorganism communities to use different substrates.